The sublime’s value in hero poems in Jahili poetry - Haddad, Mustafa; Nasir, Basheer; Tawil, Rabah (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research talks about the value of sublime being one of the aesthetic values which underlie aesthetics . The Galilee in one of the manifestations of fear and power - Based on these two principles- It can be embodied in the image of the hero , Because he faces his fear ramming it , Impervious to death , This intrusion is based on the principle of force , So is the manifestation of an individual tournament , Because the hero has a distinct recipes , Not owned by someone else . research depends on the selection of the Poetry models Describes the image of the hero Which becomes solemn Through its potential Which is trying to achieve it , And while achieved proves itself , And makes it superior to others with , And poets have legalized the language in these selected models make it sensuous standard And psychological And mental for al Jalil which the feeling self for a way to prove majesty .